„Słów kilka w obronie szlachetnego rycerza z La Manchy” – Don Kichot w wyobrażeniach młodopolan - Sadlik, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The text is devoted to selected aspects of the reception of the figure of Don Quixote in Polish literature of the late nineteenth and early twentieth century. The first part presents the history of dispute on the Spanish hidalgo, and in the two subsequent sections focus on literary incarnations of the Spanish hero penned by Jerzy Żulawski, Gabriela Zapolska and Cezary Jellenty.